2006
DOI: 10.1364/oe.14.011265
|View full text |Cite
|
Sign up to set email alerts
|

Polychromatic nonlinear surface modes generated by supercontinuum light

Abstract: We study propagation of polychromatic light near the edge of a nonlinear waveguide array. We describe simultaneous spatial and spectral beam reshaping associated with power and wavelength-dependent tunneling between the waveguides. We present experimental verifications of the effects predicted theoretically including the first observation of supercontinuum nonlinear surface modes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…Two independent studies [36][37][38] introduced a novel concept of multi-gap surface solitons (also called mixed-gap vector solitons) as mutually trapped surface states with the components associated with different spectral gaps. Garanovich et al [36] found numerically discrete surface modes in semi-infinite binary waveguide arwww.lphys.org [39] rays, which can support simultaneously two types of discrete solitons, and also analyzed different multi-gap states including the soliton-induced waveguides with the guided modes from different gaps [38] and composite vector solitons. Kartashov et al [37] studied the properties of these mixed-gap vector surface solitons in a continuum model of the interface between a uniform medium and an optical lattice imprinted in a Kerr-type nonlinear media.…”
Section: Other Generalizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two independent studies [36][37][38] introduced a novel concept of multi-gap surface solitons (also called mixed-gap vector solitons) as mutually trapped surface states with the components associated with different spectral gaps. Garanovich et al [36] found numerically discrete surface modes in semi-infinite binary waveguide arwww.lphys.org [39] rays, which can support simultaneously two types of discrete solitons, and also analyzed different multi-gap states including the soliton-induced waveguides with the guided modes from different gaps [38] and composite vector solitons. Kartashov et al [37] studied the properties of these mixed-gap vector surface solitons in a continuum model of the interface between a uniform medium and an optical lattice imprinted in a Kerr-type nonlinear media.…”
Section: Other Generalizationsmentioning
confidence: 99%
“…The colors at the [40] images represent the natural colors of the supercontinuum, except for the near-infrared part of the spectrum, which are detected as white by the camera. As the input power into the second waveguide is increased, Sukhorukov et al [39] observed enhanced coupling of red, green, and blue components to the surface waveguide (figures in [39], (b)-(e)) and the formation of polychromatic surface modes. At even higher powers the second waveguide is fully detuned from the neighboring ones and that is why light trapping is observed entirely in the second waveguide (Fig.…”
Section: Other Generalizationsmentioning
confidence: 99%
“…We also demonstrate that in the nonlinear regime, it is possible to achieve broadband all-optical switching of polychromatic light in a directional waveguide coupler with special bending of the waveguide axes. Our results suggest new opportunities for all-optical control of polychromatic light, offering additional flexibility compared to the spatial-spectral reshaping recently demonstrated experimentally in arrays of straight optical waveguides [23][24][25].…”
Section: Introductionmentioning
confidence: 62%
“…We note that the nonlinear refractive-index modulation in the detuned waveguide is only of the order of 10 ÿ4 , but it is sufficient to modify significantly the spectrum of the supercontinuum radiation. This effect is somehow similar to surface manipulation of the supercontinuum light [33], but with the ability for reconfiguration and tuning of the defect properties. Similar functionality can also be implemented by electro-optic tuning of individual waveguides of the array.…”
Section: (B)mentioning
confidence: 77%